From Action to Insight: A Professional Learning Community’s Experiences with the European Language Portfolio - Kristmanson, Paula Lee; Lafargue, Chantal; Culligan, Karla (Canadian Journal of Applied Linguistics, 2012)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-CA X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Cambria","serif"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> This paper focuses on an action research project set in the context of one professional learning community’s (PLC’s) exploration of the Common European Framework of Reference (CEFR) and the European Language Portfolio (ELP). Teachers of second and foreign languages in a large urban high school examined the potential of principles and tools related to the CEFR and ELP and shared their experiences during PLC meetings. This study examines data collected as part of the PLC discussions and deliberations and presents two particular pedagogical results emerging from this work: the development of a philosophical stance and an action plan. The paper concludes with a discussion of the process in which teachers engaged as they co-constructed understanding and explored pedagogical implications of their professional dialogue. Résumé Cet article traite d’un projet de recherche action mené dans le contexte d’une communauté d’apprentissage professionnelle (CAP) qui a exploré le Cadre européen commun de référence (CECR) et le Portfolio européen des langues (PEL) et comment la CAP les a mis en œuvre dans des classes de langue. Les enseignants des langues secondes et étrangères situés à une école secondaire urbaine ont partagé leurs expériences lors des réunions de CAP. Cette étude analyse les données recueillies lors des discussions et des délibérations de la CAP et elle présente deux résultats pédagogiques particuliers émergeant de ce travail— le développement d’une approche philosophique et un plan d’action. L’article se termine sur une discussion des processus vécus par les enseignants en co-construisant leurs connaissances pédagogiques par l’entremise du dialogue professionnel. <!–[if gte mso 9]> 0 0 1 75 429 UNB Faculty of Education (SLEC) 3 1 503 14.0 <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:Cambria; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; mso-fareast-language:JA; –> <!–[endif] –> <!–StartFragment–><!–EndFragment–>